Neuropathy scale score as an independent risk factor for myocardial infarction in patients with type 2 diabetes. Issue 7 (7th July 2022) - Wang, Lian; Guo, Simin; Wang, Weimin; Xu, Biyun; Chen, Wei; Jing, Yali; Jin, Jiewen; Li, Chenxi; Zhou, Yihua; Zhu, Dalong
Abstract: Aims: To investigate whether peripheral neuropathy scale scores are associated with myocardial infarction (MI) in patients with type 2 diabetes mellitus (T2DM). Materials and Methods: In this cross‐sectional study, 32, 463 T2DM patients were enroled from 103 tertiary hospitals in 25 Chinese provinces. Based on a history of MI, participants were divided into the MI group ( n = 4170) and the non‐MI group ( n = 28, 293). All patients were assessed using four neuropathy scales, namely, Neurological Symptom Score (NSS), Neurological Disability Score (NDS), Toronto Clinical Scoring System (TCSS), and Michigan Neuropathy Screening Instrument (MNSI), and some of the patients underwent evaluation of nerve conduction velocity (NCV) ( n = 20, 288). The relationship between these scores and myocardial infraction was analysed. Results: The neuropathy scale scores in the MI group were higher than those in the non‐MI group ( p < 0.001). After dividing patients into four groups based on the grading criteria, our results showed that, in addition to aggravating the degree of neuropathy signs, the incidence of MI increased ( p < 0.001). Logistic regression analysis results showed that neuropathy scale scores and NCV were both independent risk factors for MI ( p < 0.001). Furthermore, among the scales used, MNSI presented a higher odds ratio and area under the curve (AUC; 0.625, p < 0.001) than the other three scales (AUCNSS = 0.575, AUCNDS = 0.606, and AUCTCSS = 0.602, p < 0.001) for MI. Conclusions: Increased scores on these neuropathy scales (NSS, NDS, TCSS, and MNSI) and NCV were significantly associated with increased risk of MI and were considered independent risk factors.